(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2017)
The research aims to verifying the tax exemptions granted in accordance with the Iraqi tax legislations, showing their suitability for basic tax rules, and identifying their role to reduce the tax evasion phenomenon and the negative effects resulting therefrom, which arerepresented by a decrease in the proceeds of tax revenue and therefore leadings to a reduction of public revenues of the state. Also, the research tries to identify the ways to reduce cases of tax evasion due to their reflection positively on the public budgetof the state. The data of the research was collected through two models of questionnaires distributed to a sample of taxpayers from some professions and a sample of the tax administration staff. The research has reached a number of important results, that tax exemptions have an active role in reducing the tax evasion phenomenon, as well as that tax exemptions lead to the achievement of tax justice among taxpayers by taking into account their personal and family circumstances.